Dampak Demografi, Indeks Pembangunan Manusia, dan Demokrasi terhadap Pertumbuhan Ekonomi di Wilayah Provinsi Sulawesi Periode 2012-2022 - Ifan, Muhamad Ifan Permana; Muhammad Syaifullah; Arman; Erba Putra Diansyah; DiaMuhammad Yusuf Darasyiddin A Safa’a (Fakultas Ekonomi dan Bisnis Islam, 2024)
This research aims to analyze the impact of Demography, Human Development Index (HDI) and Democracy Index on Economic Growth in the Sulawesi Region for the 2012-2022 period. The research method used is panel data regression with the selected estimation model being the Random Effect Model (REM). The research results explain that partially demographic variables have no impact on economic growth, HDI has a significant impact on economic growth and the democracy index (X3) has no impact on economic growth. Simultaneously the demographic variables (X1), HDI (X2) and democracy index (X3) have an impact on the economic growth variable (Y) with a coefficient of determination (R2) of 0.18%, The research results show that the impact of demographics, HDI and index democracy is only 18% while 82% is influenced by other variables.